2021
DOI: 10.1038/s41598-021-97771-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal choriocapillaris changes in the presence of reticular pseudodrusen

Abstract: To determine longitudinal changes in choriocapillaris (CC) measures in eyes with reticular pseudodrusen (RPD) using optical coherence tomography angiography (OCTA). In this observational prospective study, 20 patients with exclusively RPD and no other alteration due to age-related macular degeneration were included. Eight RPD patients were re-examined at 5-year follow-up. Multimodal imaging was performed at baseline and at 5-year follow-up. OCTA CC images were analyzed for number, size and total area of flow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Likewise, choroidal thinning is a characteristic in eyes with RPDs/SDDs and geographic atrophy [ 68 , 102 , 103 , 104 ]. Several in vivo studies confirmed a marked alteration in choroidal parameters in eyes with RPDs/SDDs, using choroidal thickness, choroidal vascular thickness, choroidal vascularity index (CVI), and optical coherence tomography angiography (OCTA) [ 105 , 106 , 107 , 108 , 109 , 110 ]. Although most of the existing literature reported a thinner choroid in eyes with SDDs, some studies did not observe choroidal thinning between AMD eyes and SDDs, suggesting a non-univocal association between SDDs and choroidal thickness [ 84 , 85 ].…”
Section: Choroidal Imaging and Assessment In Vivomentioning
confidence: 99%
“…Likewise, choroidal thinning is a characteristic in eyes with RPDs/SDDs and geographic atrophy [ 68 , 102 , 103 , 104 ]. Several in vivo studies confirmed a marked alteration in choroidal parameters in eyes with RPDs/SDDs, using choroidal thickness, choroidal vascular thickness, choroidal vascularity index (CVI), and optical coherence tomography angiography (OCTA) [ 105 , 106 , 107 , 108 , 109 , 110 ]. Although most of the existing literature reported a thinner choroid in eyes with SDDs, some studies did not observe choroidal thinning between AMD eyes and SDDs, suggesting a non-univocal association between SDDs and choroidal thickness [ 84 , 85 ].…”
Section: Choroidal Imaging and Assessment In Vivomentioning
confidence: 99%
“…Previous research indicated that eyes with SDD have reduced visual acuity and greater choriocapillaris impairment, compared to eyes with drusen and lacking SDD. 17 , 18 A 5-year longitudinal study showed that both SDD-affected and unaffected areas can be associated with choriocapillaris impairment. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 A 5-year longitudinal study showed that both SDD-affected and unaffected areas can be associated with choriocapillaris impairment. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 It is also in contrast to previous observations that eyes with RPD had a larger proportion of the total FD area accounted for by FDs ≥ 10,000 µm 2 in one study, 54 or more individual areas of larger FDs in another study. 55 These differences may be attributed to differences in CC flow impairments between eyes with large drusen and coexistent RPD and eyes with only RPD.…”
Section: Discussionmentioning
confidence: 99%